Different approaches to learning science, technology, engineering, and mathematics case studies from Thailand, the Republic of Korea, Singapore, and Finland. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
STEM education has an important role in inclusive and equitable quality education and lifelong learning opportunities for all. By utilizing an inquiry based and experiential teaching and learning approach as well as integrating engineering and technology with science and mathematics, STEM promotes employability skills, entrepreneurship, and innovation. The case studies in this publication provide inspiration and lessons for ADB developing member countries to enhance their respective STEM education programs.
Keywords: Interdisciplinary approach in education; Education, Secondary--Curricula.; Electronic book